Fabrication and characterization of ZnO/Se1-x Te x solar cells - Jiajia Zheng; Liuchong Fu; Yuming He; Kanghua Li; Yue Lu; Jiayou Xue; Yuxuan Liu; Chong Dong; Chao Chen; Jiang Tang (Frontiers of Optoelectronics, 2022)
Abstract Selenium (Se) element is a promising light-harvesting material for solar cells because of the large absorption coefficient and prominent photoconductivity. However, the efficiency of Se solar cells has been stagnated for a long time owing to the suboptimal bandgap (> 1.8 eV) and the lack of a proper electron transport layer. In this work, we tune the bandgap of the absorber to the optimal value of Shockley–Queisser limit (1.36 eV) by alloying 30% Te with 70% Se. Simultaneously, ZnO electron transport layer is selected because of the proper band alignment, and the mild reaction at ZnO/Se0.7Te0.3 interface guarantees a good-quality heterojunction. Finally, a superior efficiency of 1.85% is achieved on ZnO/Se0.7Te0.3 solar cells. Graphical abstract